Is Land Really Unique?: Revisiting Specific Performance as the Default Remedy for Land Sale Contracts in New Zealand - Abdussalam, Moshood (Victoria University of Wellington Law Review, 2024)
The argument put forth in this article is that land sale contracts, unless proven to possess unique characteristics, are not inherently different from other types of contracts. The article proposes a shift from treating specific performance as the default remedy for enforcing land sale contracts. Instead, the remedy of specific performance should be considered applicable only in exceptional situations, as is the case for contracts generally. The article also addresses the nature of damages in lieu of specific performance and suggests a reconsideration of how that remedy applies to land sale contracts.<span class="EOP SCXW106721359 BCX0" data-ccp-props=""201341983":1,"335551550":6,"335551620":6,"335559731":0,"335559739":160,"335559740":260,"335572071":6,"335572072":4,"335572073":4278190080,"335572079":6,"335572080":4,"335572081":4278190080,"469789798":"single","469789806":"single"">